Vajravārāhī in Khara Khoto and Prajñāpāramitā in East Java: Connected by Pearl Ornaments - Lesley S Pullen (Religions)
This research, situated in the geographical and historical context of the Tangut and East Java, uncovers a significant aspect of the evolution of Buddhist art styles. A thangka of the goddess Vajravārāhī found in Khara Khoto, dated to the late 12th century, shows the bodhisattva decorated with a pearl-chain girdle and upper-arm bands. This form of pearl-chain jewellery, which appears on Vajravārāhī and other Sino-Tibetan-style bodhisattvas, also appears on three stone statues of the goddess Prajñāpāramitā in East Java, all of which depict a near identical use of this pearl-chain ornamentation, as well as on a statue of Prajñāpāramitā at the Muara Jambi Buddhist site in Sumatra. Maritime trade between the regions of China and Java was extensive. The commonality of such motifs in China and Java may highlight a convergence of cultural forces and perhaps shared styles originating from the maritime realm and traded via maritime routes; however, a direct or indirect influence of Sino-Tibetan styles on thangka paintings featuring this depiction of the jewellery perhaps occurred following dynamics of north–south exchange, highlighting the interrelated links along maritime and overland routes through the Pāla Buddhist kingdom in eastern India. Thus, I propose that the connection between the Vajravārāhī and other Tibetan thangka paintings was inspired by Northeast Indian influence from the Hexi corridor, eventually reaching East Java.